2004
DOI: 10.1523/jneurosci.1344-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

An Attenuated Immune Response Is Sufficient to Enhance Cognition in an Alzheimer's Disease Mouse Model Immunized with Amyloid-β Derivatives

Abstract: Immunization with amyloid-␤ (A␤) 1-42 has been shown to reduce amyloid burden and improve cognition in Alzheimer's disease (AD) model mice. In a human trial, possible cognitive benefit was found but in association with significant toxicity in a minority of patients. We proposed that immunization with nonfibrillogenic A␤ derivatives is much less likely to produce toxicity and have previously shown that one such derivative (K6A␤1-30) can reduce amyloid burden in mice to a similar extent as A␤1-42. Here, we immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
167
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(176 citation statements)
references
References 34 publications
(52 reference statements)
8
167
1
Order By: Relevance
“…Recently, several groups have demonstrated that active immunization of amyloid precursor protein (APP) transgenic (Tg) mice with fibrillar Aβ, as well as passive transfer of anti-Aβ antibodies, significantly reduced Aβ plaque deposition, neuritic dystrophy, and astrogliosis in the brains of these mice (Schenk et al, 1999;Bard et al, 2000;Morgan et al, 2000;Wilcock et al, 2004a). Improvements in learning and memory were also observed after either active or passive immunization of APP/Tg mice (Janus et al, 2000;Morgan et al, 2000;Dodart et al, 2002;Sigurdsson et al, 2004;Wilcock et al, 2004a;2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups have demonstrated that active immunization of amyloid precursor protein (APP) transgenic (Tg) mice with fibrillar Aβ, as well as passive transfer of anti-Aβ antibodies, significantly reduced Aβ plaque deposition, neuritic dystrophy, and astrogliosis in the brains of these mice (Schenk et al, 1999;Bard et al, 2000;Morgan et al, 2000;Wilcock et al, 2004a). Improvements in learning and memory were also observed after either active or passive immunization of APP/Tg mice (Janus et al, 2000;Morgan et al, 2000;Dodart et al, 2002;Sigurdsson et al, 2004;Wilcock et al, 2004a;2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence demonstrated the ability of the immune system to generate Abs after immunization against A␤ that may promote removal of A␤ from the brain (7)(8)(9)(10)(11). Besides the Ab-mediated systemic adaptive response, increasing studies suggest that the T cell immune response may be involved in the inflammation process of AD (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…We designed these homologous peptides so that they still have a high binding affinity to wild-type A␤ peptides and also have a similar BBB permeability. In prior studies we have shown that these A␤ homologous peptides do not self-assemble or promote the fibrillization of endogenous A␤ peptides (Asuni et al, 2006;Sigurdsson et al, 2001Sigurdsson et al, , 2004a). In the current study we used K6-A␤1-30 chelated to gadolinium via incorporation of DPTA at the amino terminus.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, we developed a compound, Gd-DTPA-K6A␤1-30, that does not form amyloid aggregates and is non-toxic while maintaining high affinity for A␤. We have previously used K6A␤1-30 and related derivatives as experimental vaccines against AD (Sigurdsson et al, 2001(Sigurdsson et al, , 2004a. In this report we have evaluated the utility of this A␤ homologous peptide, which has therapeutic potential as a vaccine, for a dual use as a MRI contrast agent, when coupled with gadolinium.…”
Section: Introductionmentioning
confidence: 99%